Prospects of Handloom Industries in Pabna, Bangladesh (Global Journal of Management and Business Research, 2013)
Handloom industry in Bangladesh is having glorious past, questionable present and blurry future due to a lot of internal and external factors that are acting behind the scene. In this paper we tried to identify the prospects of Handloom industry in Pabna, Bangladesh. In this case study we identify all the internal & external factors that are great contribution to realize the true present conditions of the Handloom industry in Pabna, Bangladesh. In field study, we fell that there are some predetermined factors, like -shortage of working capital, high cost of raw materials, lack of organizing capability, inadequate technology & efficiency, lack of policy support, great knowledge gap, lack of power supply and shortage of credit facilities, those are the main forces that directly hit the Handloom industry in Pabna, Bangladesh.
Keywords: handloom Industry; sample size; collection method; handloom products